(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The revival of Silk Road tourism in Uzbekistan has become a cornerstone of the country’s socio-economic modernization strategy. Grounded in sustainable tourism and heritage conservation theories, this article explores evidence-based developments in infrastructure, policy, digital transformation, and community involvement. The analysis concludes that integrating cultural authenticity, digitalization, and participatory management is essential for ensuring the sustainable revival of the Silk Road in Uzbekistan.